The Modified painDETECT Questionnaire for Patients with Hip or Knee Osteoarthritis: Translation into Dutch, Cross-Cultural Adaptation and Reliability Assessment. - Wietske Rienstra; Tim Blikman; Frans B Mensink; Jos J A M van Raay; Baukje Dijkstra; Sjoerd K Bulstra; Martin Stevens; Inge van den Akker-Scheek (PLoS ONE, 2015)
There is a growing amount of evidence that alteration in pain processing by the peripheral and central nervous system play a role in osteoarthritis pain, leading to neuropathic-like symptoms. It is essential to identify knee and hip osteoarthritis patients with a neuropathic pain profile in order to offer such patients education and additional treatment options besides conventional pain treatment. The painDETECT Questionnaire is a self-report questionnaire developed to discriminate between nociceptive and neuropathic pain. This questionnaire was modified to fit patients suffering from knee osteoarthritis. The aim of this study was to translate and cross-culturally adapt the modified painDETECT Questionnaire to the Dutch language and to provide a modified version to fit patients with hip osteoarthritis. Reliability for internal consistency, repeatability and floor and ceiling effects were subsequently assessed. A total of 278 patients were included in the reliability study and 123 patients in the repeatability analysis. The Dutch modified painDETECT Questionnaire shows good internal consistency and small relative measurement errors, represented by a good intraclass correlation coefficient. Absolute measurement error, represented by the Standard Error of Measurement, was acceptable. However, a measurement bias might be present when it comes to repeatability. To our knowledge, this study is the first to provide a Dutch modified painDETECT Questionnaire to fit hip and knee osteoarthritis patients and to assess internal consistency, reliability and agreement. International guidelines were followed in the translation process and this study has ample sample size with an adequate time interval for repeatability. Based on this study, the Dutch modified painDETECT Questionnaire seems to be fit as a discriminative tool to identify knee and hip osteoarthritis patients with a neuropathic pain profile. Whether it is also suitable as an evaluative tool to record changes over time or after an intervention remains open to further investigation.